Evaluating Students’ Voices in Their Outfit Reviews: An Appraisal Analysis - Yuni Awalaturrohmah Solihah (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
This study evaluated the language use in students’ speaking production. It was aimed to classify and analyze the level of attitude as one of subsystems appraisal theory proposed by Martin and White (2005). The attitude subsystem focused on the choice of words, phrases and structure by speakers to convey their reviews on an issue. The data were taken from 30 students’ reviews of presentation about outfit in a private university in Cirebon through descriptive qualitative method with spoken discourse analysis. The data were taken by transcribing the recorded students’ reviews into text, classifying into the clauses and analyzing the appraising items to conclude the attitude resources in the students’ reviews. The finding of this study demonstrates that appreciation is the most dominant used in students’ reviews to convey their representation to the things toward the outfit presentation. That makes their reviews are appreciative than emotional and judgemental to express their opinion about outfit presentation. This study suggests English lecturers to informs students the importance of attitudinal words usage in order to strengthen their voices, especially in speaking.